Isolation and Identification of Vibrio cholerae causes Epidemic cholera 2007 in Iraq by Rapid Method (Immunochromatographic one step rapid visual test) and comparing it with the traditional Bacterlogical Methods (Baghdad Science Journal, 2025)
This study was for searching for Cholera Bacteria serotype which causes epidemiology Cholera in the 2007 in a fast method which contains (Rapid Visual Test) (Crystal V.C.) which was used for the first time in Iraq to diagnosis of Cholera Bacteria & compared with the traditional bacteriology method.The Cholera disease is one of the most dangerous epidemiological diseases which lead to death with a percentage of (50 – 70) % in the severe cases for untreated patients .For this purpose, 100 samples of stool from the patients from a (13) hospitals in Baghdad Governorate in the period from August to the end of December. The Cholera was diagnosis in two methods, 1st method was the fast method using the nitrocellulose which is coated with anti-body of Cholera Bacteria .The results was compared with the 2nd method which depends on the cultural characteristics of the cultural media, also the bacteria was diagnosis using the biochemical inspects by the system of API 20E in addition to the using of antisera to specify serotype& sub-serotype ( Monovalent, Polyvalent(O1) .Also, the relation between the disease & the months in the year in which the disease appear was studied. The results show the ability to isolate & identifecate (78) isolate for the serotype (01) in the fast method ( Rapid Visual Test ) ( Crystal V-C ) , & after the bacteriology inspects on these (78) isolate the all isolates were belongs for Cholera Bacteria of the serotype (01) till the sub-serotype , all the (78) isolates were belongs to the sub-serotype (Inaba). The results show, the most infection was in September (36) , & October (22).